Evaluation of E-health literacy in Paramedicine and Health Nutrition students of Lorestan University of Medical Sciences - Mahnaz Samadbeik; Marzieh Saremian; Maryam Sohrabizadeh; Mehdi Birjandi; Saeideh Garavand (Mashhad University of Medical Sciences, 2020)
Background and Objective: There is a gap between access to eHealth resources and the skills of consumers to use them, which can help to provide quality eHealth by identifying these skills. The aim of this study was to determine the electronic health literacy score of Lorestan University of Medical Sciences students in 2018. Materials and Methods: This descriptive-analysis study was conducted on students of the faculties of Paramedicine, Health and Nutrition at Lorestan University of Medical Sciences in the first semester of 2018-2019. The sampling method was stratified random in proportion to the volume was employed. Data were collected using a questionnaire, which consisted of five parts (Demographic Characteristics, Educational Features, Internet usage questions, Electronic Health Literacy Scale Tool Questions). The Content validity of questionnaire was assessed in an interview with 3 health education experts and 4 health information experts. The reliability of the questionnaire was assessed using Cronbach's alpha (overall Cronbach's alpha was 0.89) Data analysis was conducted with SPSS version 21 statistic software package and descriptive statistics, independent t-test, Pearson correlation coefficient, ANOVA and Duncan's post hoc tests. Results: According to the results of this study, the students had a good level of health literacy. There is also a significant difference between the level of health literacy of those access the Internet outside the college and those do not (p<0.05). In addition, the most common place to use the Internet was the dormitory (% 43.8). Conclusion: Planning for more to access the Internet outside of college for the students, especially in dorms, can help to improve students' health literacy. In addition, conducting workshops on how to search for electronic health information as well as introducing reliable sources and databases can be effective in enhancing students' health literacy